Cytotoxic Activity of Endophytic Fungus against HeLa Cells (Cervical Cancer Cells): A Article Review - Suryani, Fitri; Aulia Bakhtra, Dwi Dinni; Fajrina, Anzharni (Asian Journal of Pharmaceutical Research and Development, 2022)
Cancer is one of the leading causes of death in every country worldwide. It has been growing rapidly every year. One type of cancer is cervical cancer. Cervical cancer fourth rank suffered in women worldwide after endometrial, colorectal, and breast cancer. This review article aims to summarize and describe several research reports of endophytic fungi and their cytotoxic activity against HeLa cells (cervical cancer cells). This article review was made by conducting a literature study. Literature is collected from various sources such as official pharmaceutical scientific books, national and international journals published in the last twenty years. Endophytic fungi play an important role in providing a constant supply of anticancer with minimal side effects and high target specificity at an affordable cost.Therefore, it is necessary to explore and utilize the compounds contained in endophytic fungi. Further research on endophytic fungi needs to be done to find new drug candidates to fight deadly diseases in humans such as cervical cancer.